Think-aloud protocol of ESL undergraduates in writing / Fong Seok Ching - Fong, Seok Ching (2015)
This study investigates the cognitive processes of five Chinese ESL undergraduates from University of Malaya (UM) by using Think-Aloud Protocols (TAPs) as the main research tool. The participants of this study are Band Three achievers in Malaysian University English Test (MUET) and they are required to write formal and informal letters on different assigned time slots. Apart from TAPs, data are also collected through interview and questionnaires from the participants to triangulate the results of study. The data findings obtained have successfully answered the research questions and achieved the objectives of the study, i.e. (i) to identify the thought processes related to writing as the respondents engage in formal and informal letter writing; (ii) to investigate the differences in cognitive processes between formal and informal letter writing (if any); (iii) to find out the factors affecting their cognitive processes during the writing duration for both types of letters. An additional writing category is added to Wang and Wen (2002)’s coding system, which is “Emotional-expressing”. Results of the study also state that there are five major factors contributing to challenges faced by ESL undergraduates, namely, lack of English vocabulary, poor grammar mastery, types of writing task, other language (Malay/Mandarin) interference, and personal preference. Although there is no stark difference found between the cognitive processes in formal and informal letter composing tasks, it is noticed that participants are generally more focused and organised in composing the former. Additionally, Emotion-expressing is found to occur more frequently in the preferred task. Keywords: Think-Aloud Protocols (TAPs), writing